CHILDHOOD VACCINATION: MEDICAL BENEFITS, PUBLIC HEALTH IMPACT, AND PARENTAL RESPONSIBILITIES - Asatullyev Rustam; Xudoynazarova Xadisa (TADQIQOTLAR, 2026)
Abstract: Childhood vaccination represents one of the most successful public health interventions in modern medical history. This article provides a comprehensive analysis of childhood vaccination, examining its medical efficacy, safety profile, public health impact, current global coverage trends, and the complex legal and ethical considerations surrounding parental decision-making. Drawing on recent Cochrane reviews, WHO and UNICEF data, and contemporary legal scholarship, this article demonstrates that vaccines have prevented hundreds of millions of illnesses and millions of hospitalizations over the past three decades. However, declining vaccination rates in several countries threaten herd immunity and have led to the resurgence of previously controlled diseases such as measles. The article also explores the legal framework governing childhood vaccination, particularly the tension between parental autonomy and children’s rights to health protection. The evidence overwhelmingly supports vaccination as a safe, effective, and cost-effective intervention that benefits not only individual children but entire communities.